Developing Countries and the Multilateral Trading System after Doha - T. N. Srinivasan (Yale University, Economic Growth Center, 2002)
The Fourth Session of the Ministerial Conference of the World Trade Organization (WTO), held in Doha, Qatar, in November 2001, launched a new round of multilateral trade negotiations (MTN) and a work programme (WP) for the WTO involving the negotiating agenda and steps for meeting the challenges facing the multilateral trading system. The paper evaluates the WP, in particular, whether it would redress the unfavourable balance between benefits and costs to developing countries DCs of the agreement that concluded the previous (Uruguay) round of MTN. It discusses the failure of the third session in Seattle to launch a new round in December 1999, and also documents the unfavourable balance. While concluding that with adequate preparation, the negotiators could reach an agreement in the new round yielding substantial gains to DCs, the paper also suggests possible negotiating points for DCs.
Keywords: F02; F13; F15; F16; F18; O19; O34; 330; World Trade Organization (WTO); Multilateral Trade Negotiations; Developing Countries; Antidumping; Trade Related Intellectual Property Services (TRIPS); Trade and Labour Standards; Trade and Environment; Preferential Trade Agreements; Internationale Wirtschaftsorganisation; Internationale Handelspolitik; Entwicklungsländer; Welt